Effect of hybrid combinations of Erythroxylum revolutum Mart. leaf ethanolic extract or alkaloid-enriched fraction with antibiotic drugs against multidrug-resistant bacteria strains - Maísa F.S. Barbosa; Paulo H.O. Miranda; Carlos A. Souza; Clécio S. Ramos; André L. Melo; Janaína E. Rocha; Camila F. Bezerra; Maria S. Costa; Helenicy N.H. Veras; Henrique D.M. Coutinho; Irwin R.A. Menezes; Rogério A. Saraiva (Elsevier, 2021)
Background The combination between antibiotic drugs and extracts derived from medicinal plants is one of the promising strategies against multidrug-resistant (MDR) bacterial strains to overwhelm the antimicrobial resistance.Hypothesis/Purpose We aimed to evaluate the antibacterial effect of hybrid combinations of ethanolic extract (EREE) or alkaloid-enriched fraction (ERAF) obtained from Erythroxylum revolutum leaves and conventional antibiotic drugs.Methods We tested the antimicrobial activity of EREE and ERAF in vitro against gram-positive (Staphyloccocus aureus) and Gram-negative (Escherichia coli and Pseudomonas aeruginosa) standard and MDR strains. Additionally, we performed phytochemical studies using GC/MS, 1H, 13C NMR spectra, and two-dimensional techniques.Results Although the minimum inhibitory concentration (MIC) values of EREE or ERAF alone against bacterial growth were ≥ 1024 µg/ml, we denoted a total synergism effect in the hybrid combinations ERAF + gentamicin, ERAF + norfloxacin, and ERAF + erythromycin against MDR S. aureus strain, with a significant MIC reduction of 84.7%, 75.0%, and 89.85%, respectively. Although EREE demonstrated a total synergism effect in the hybrid combination gentamicin + EREE (with a significant decrease of MIC of 68.8%), on the contrary, EREE also elicited a strong antagonist effect in some hybrid combinations against the MDR bacteria strains tested. Phytochemical studies revealed in ERAF the presence of two tropane alkaloids described for the first time in the family Erythroxylaceae: 6-(2'-methylbutyryloxy)-3-hydroxytropane (87.07%) and 6-butyryloxy-3-hydroxytropane (12.93%).Conclusion Together, these data can highlight the first evidence of enriched-alkaloid fractions of E. revolutum in hybrid combinations with antibiotics, and propose tropane alkaloids from E. revolutum as new potential candidates in drug combinations for the treatment of infections caused by MDR S. aureus, which is one of the main agents causing infections with death worldwide.